2021
DOI: 10.1098/rsos.201110
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trace metal cations and absorbed water on colour transition of turquoise

Abstract: Thirty-five gem-quality turquoise samples with various colours were investigated using energy-dispersive X-ray fluorescence spectroscopy, ultraviolet–visible spectroscopy, Fourier-transform infrared spectroscopy and scanning electron microscopy. Sample chemical and spectral analyses indicate that Fe 3+ contributes to green hue of turquoise, whose absorption band exhibits a bathochromic shift from 426 to 428 nm with increasing V content in the solid-solution series turquoise-chalcosideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…To better ensure the accuracy of grading the colored gemstones, it is necessary to determine the objective grading environment. The CIE1931 color space system was first introduced to the color quantification study in gemology, however, to solve the problem that this system is inconsistent with the human visual perception [25], the CIE1976 L * a * b * uniform color space was born and applied to the quantitative characterization of gems which have been used extensively, such as sapphire [26], peridot [14], jadeite [13,[27][28][29], tourmaline [30,31], alexandrite [32], amethyst [33], turquoise [34], chrysoprase [35], garnet [36], beryl [37], etc. Based on the CIE1976 color space, Tang et al and Jiang et al analyzed the influence of Munsell neutral grey backgrounds on peridot and chrysoprase, respectively, and concluded that the background with high lightness was highly applicable to help distinguish the color of gems [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…To better ensure the accuracy of grading the colored gemstones, it is necessary to determine the objective grading environment. The CIE1931 color space system was first introduced to the color quantification study in gemology, however, to solve the problem that this system is inconsistent with the human visual perception [25], the CIE1976 L * a * b * uniform color space was born and applied to the quantitative characterization of gems which have been used extensively, such as sapphire [26], peridot [14], jadeite [13,[27][28][29], tourmaline [30,31], alexandrite [32], amethyst [33], turquoise [34], chrysoprase [35], garnet [36], beryl [37], etc. Based on the CIE1976 color space, Tang et al and Jiang et al analyzed the influence of Munsell neutral grey backgrounds on peridot and chrysoprase, respectively, and concluded that the background with high lightness was highly applicable to help distinguish the color of gems [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are mainly based on the subjective evaluation of the color by the operator, so it takes a lot of time and money to train professional graders. UV–Vis spectrophotometers can provide accurate absorption spectra from which color calculations can be made 2 , 3 ; however, the complex conversion process has hindered their development in gemstone color measurement; hand-held spectrophotometers, as the mainstream gem color measurement tool at present, has been used to measure the color of jadeite green 4 , jadeite red 5 , 6 , turquoise 7 , peridot 8 , 9 , amethyst 10 , chrysoprase 11 , 12 , and extensive gemstone chromatography studies. Because of its convenient operation and reliable data, this tool has already been favored by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GIA has used the Munsell system to form a set of independent and mature colour classification methods, such as yellow, pink, blue, and Cape series diamonds colour grading [14][15][16][17]. Many scholars studied the colour of gemstones based on the CIE1976 L*a*b* uniform colour space system, including jadeite [18], peridot [19,20], garnet [21][22][23], tourmaline [24,25], amethyst [26], and turquoise [27].…”
Section: Introductionmentioning
confidence: 99%